2005
DOI: 10.1007/s10120-005-0334-7
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic breast cancer presenting as linitis plastica of the stomach

Abstract: Early detection and treatment of breast cancer, leading to longer survival, has revealed the natural history of this disease process. Linitis plastica of the stomach is a potential long-term sequela of metastatic breast cancer. Here we present a case of metastatic breast cancer presenting as linitis plastica, as well as the treatment algorithm for this rare clinical entity. The world literature describes a clear pattern of linitis plastica for metastatic infiltrating lobular breast cancer and a discrete nodula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 3 publications
(4 reference statements)
0
9
0
Order By: Relevance
“…Other authors showed that the most common type of gastric metastasis of breast cancer (73-83%) is linitis plastica (34)(35)(36).…”
Section: Diagnosticmentioning
confidence: 99%
“…Other authors showed that the most common type of gastric metastasis of breast cancer (73-83%) is linitis plastica (34)(35)(36).…”
Section: Diagnosticmentioning
confidence: 99%
“…Though metastatic breast cancer to the stomach is rare, invasive lobular subtypes are known to metastasize to the gastrointestinal tract and can occur years after the initial cancer treatment [ 1 4 ]. Clinical manifestations can be vague with varying endoscopic and radiologic appearances, with diffuse infiltrating disease most commonly seen [ 5 7 ]. Endoscopic mucosal biopsies often confirm the diagnosis, though some patients require deep biopsies or surgical biopsies due to tumor infiltration of layers deep to the mucosa [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ILC metastasis to the stomach was more frequent when considering pathological type. There are several case reports including only a few cases due to low incidence of breast cancer with gastric metastasis (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Taal et al (21) reported 51 cases of breast cancer with gastric metastasis, and 36 of the 51 patients had ILC.…”
Section: Discussionmentioning
confidence: 99%
“…The most common metastatic sites of breast cancer are the bone, brain, liver and lung, however, patterns of metastasis are affected by the breast cancer subtype (3)(4)(5). By contrast, breast cancer rarely metastasizes to the gastrointestinal tract, including the stomach, and few studies and case reports concerning gastric metastasis from breast cancer can be found (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). Chemokines and their receptors, including CXCR4 and CCR7, are critical for regulating the location of metastasis.…”
Section: Introductionmentioning
confidence: 99%